Oral toxicity of arjunolic acid on hematological, biochemical and histopathological investigations in female Sprague Dawley rats - Aamir, Khurram; Khan, Hidayat Ullah; Hossain, Chowdhury Faiz; Afrin, Mst. Rejina; Shaik, Imam; Salleh, Naguib; Giribabu, Nelli; Arya, Aditya (PeerJ, 2019)
Background: Arjunolic acid (AA) is a potent phytochemical with wider pharmacological activities. Despite potential medicinal properties on various in vitro and in vivo studies, there is still a dearth of scientific data related to its safety profile and toxicological parameters. The current study aimed to investigate acute toxicity of AA in normal female Sprague Dawley rats. Methods: In this study, AA was administered orally at an individual dose of 300 and 2000 mg/kg body weight to group 1 and 2 respectively, while group 3 served as normal control. All the animals were observed for 2 weeks to determine any behavioral and physical changes. On day 15, blood was collected for hematological and biochemical investigation, later animals from all the three groups were euthanized to harvest and store essential organs for histopathological analysis. Four different staining techniques; hematoxylin and eosin, Masson trichrome, Periodic acid Schiff and Oil O Red were used to investigate any alterations in different tissues through microscopical observation. Results: The results of the study showed no morbidity and mortality at two different dosage of AA treatment. Daily food &water intake, body weight, relative organ weight, hematological and biochemical parameters were detected to be normal with no severe alteration seen through microscopical investigation in the structure of harvested tissues. Our findings support the safety profile of AA, which was well tolerated at higher dose. Thus, an in-detail study on the subacute disease model is warranted. © 2019 Aamir et al.